Kaplan & Sadock's synopsis of psychiatry : behavioral sciences/clinical psychiatry - Sadock, Benjamin J., 1933-; Sadock, Virginia A.; Ruiz, Pedro, 1936- (Philadelphia : Wolters Kluwer, 2015)
'The goal of this book is to foster professional competence and ensure the highest quality care to those with mental illness. An eclectic, multidisciplinary approach has been its hallmark; thus, biological, psychological, and sociological factors are equitably presented as they affect the person in health and disease'--Provided by publisher.
Neural sciences -- Contributions of the psychosocial sciences -- Contributions of the sociocultural sciences -- Theories of personality and psychopathology -- Examination and diagnosis of the psychiatric patient -- Classification in psychiatry -- Schizophrenia spectrum and other psychotic disorders -- Mood disorders -- Anxiety disorders -- Obsessive-compulsive and related disorders -- Trauma- and stressor-related disorders -- Dissociative disorders -- Psychosomatic medicine -- Chronic fatigue syndrome and fibromyalgia -- Feeding and eating disorders -- Normal sleep and sleep-wake disorders -- Human sexuality and sexual dysfunctions -- Gender dysphoria -- Disruptive, impulse-control, and conduct disorders -- Substance use and addictive disorders -- Neurocognitive disorders -- Personality disorders -- Emergency psychiatric medicine -- Complementary and alternative medicine in psychaitry -- Other conditions that may be a focus of clinical attention -- Physical and sexual abuse of adults -- Psychiatry and reproductive medicine -- Psychotherapies -- Psychopharmacological treatment -- Brain stimulation methods -- Child psychiatry -- Adulthood -- Geriatric psychiatry -- End-of-life issues -- Public psychiatry -- Forensic psychiatry and ethics in psychiatry -- World aspects of psychiatry.
Preceded by Kaplan & Sadock's synopsis of psychiatry / Benjamin James Sadock, Virginia Alcott Sadock. 10th ed. 2007.
Includes bibliographical references and index.
Keywords: Mental disorders